2022
DOI: 10.3390/w14050723
|View full text |Cite
|
Sign up to set email alerts
|

Different Assembly Patterns of Planktonic and Sedimentary Bacterial Community in a Few Connected Eutrophic Lakes

Abstract: The mechanism of bacterial community assembly has been the hot spot in the field of microbial ecology and it is difficult to quantitatively estimate the influences of different ecological processes. Here, a total of 23 pairs of planktonic and sedimentary samples were collected from five lakes in Wuhan, China. significant higher α-diversity (p < 0.001) and β-diversity (p < 0.001) of bacterial communities were observed in sediment than those in water. Some phylum had linear relationships with the comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…Previous studies ( Jiao et al, 2020 , 2021 ; Xia et al, 2022 ) have shown that bacterial sediment communities and water column communities were structured differently with homogeneous selection being more prominent in the water column in comparison to the sediment. This pattern was observed for both bacteria and eukaryotes although homogeneous selection was not the dominant process for bacteria in the water column.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies ( Jiao et al, 2020 , 2021 ; Xia et al, 2022 ) have shown that bacterial sediment communities and water column communities were structured differently with homogeneous selection being more prominent in the water column in comparison to the sediment. This pattern was observed for both bacteria and eukaryotes although homogeneous selection was not the dominant process for bacteria in the water column.…”
Section: Discussionmentioning
confidence: 92%
“…Biological communities present within the sediments are also vital in many biogeochemical processes ( Forsberg, 1989 ). Studies investigating community patterns in both the water column and sediments are notably fewer and focused mostly on differences in bacterial communities between the two habitats ( Zeng et al, 2019 ; Jiao et al, 2020 , 2021 ; Xia et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results agree with analyses of microbial communities within the surface sediments (first few cm) of lakes in other regions. In these studies, variable selection, driven by environmental differences, created differences among communities (Jiao et al, 2021; Pearman et al 2022, b; Xia et al, 2022; Yang et al, 2020; Zeng et al, 2019). Specifically, water nutrients, algal concentrations, and pH have been suggested to cause a strong selection of sediment bacteria (Jiao et al, 2021; Pearman, Adamson, et al, 2022; Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%